2021
DOI: 10.1111/ajr.12702
|View full text |Cite
|
Sign up to set email alerts
|

Rural emergency departments: A systematic review to develop a resource typology relevant to developed countries

Abstract: Objective Despite low patient numbers, rural emergency departments have a similar diversity of case presentations as urban tertiary hospitals, with the need to manage high‐acuity cases with limited resources. There are no consistent descriptions of the resources available to rural emergency departments internationally, limiting the capacity to compare clinical protocols and standards of care across similarly resourced units. This review aimed to describe the range of human, physical and specialist resources de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…3 Facilities in rural regions were also substantially smaller with reduced levels of infrastructure that may not be adequate for managing all surgical emergencies. 3,6 The disparity of healthcare in regional Australia is a recognized problem, that has been difficult to address within the current healthcare system. The Australian healthcare system, Medicare, is a universal healthcare insurance scheme available to Australian citizens, permanent residents and countries with reciprocal agreements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Facilities in rural regions were also substantially smaller with reduced levels of infrastructure that may not be adequate for managing all surgical emergencies. 3,6 The disparity of healthcare in regional Australia is a recognized problem, that has been difficult to address within the current healthcare system. The Australian healthcare system, Medicare, is a universal healthcare insurance scheme available to Australian citizens, permanent residents and countries with reciprocal agreements.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of specialists was considered by patients in rural and remote regions to be the greatest barrier to accessing healthcare 3 . Facilities in rural regions were also substantially smaller with reduced levels of infrastructure that may not be adequate for managing all surgical emergencies 3,6 . The disparity of healthcare in regional Australia is a recognized problem, that has been difficult to address within the current healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Additionally, GPs may vary considerably in their own availability, resources and infrastructure, skill-mix and/or sub-specialisation, local population case-mix, demands, needs and dynamics such as availability of public transport and proximity to ancillary services. 30 The findings have implications for care coordination and patient navigation. The five factors identified that do influence the patient's confidence in the nurses' assessment may inform the…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that using retrospective data fails to properly take into account a number of factors such as the patients' subjective views on the gravity of their conditions, patient's choice where to seek care and the actual and perceived local resource availability 28,29 . Additionally, GPs may vary considerably in their own availability, resources and infrastructure, skill‐mix and/or sub‐specialisation, local population case‐mix, demands, needs and dynamics such as availability of public transport and proximity to ancillary services 30 …”
Section: Discussionmentioning
confidence: 99%
“…Our research on the expanded role of PHC as a suitable alternative to the ED for acute care explored the factors influencing the growth in demand for emergency healthcare 2,5,10–13 . One of the research outcomes was the potential to divert demand to PHC, but that would require significant re‐engineering of PHC to meet patient needs 14 .…”
Section: Introductionmentioning
confidence: 99%